A cross-sectional survey of coronary plaque composition in individuals on non-statin lipid lowering drug therapies and undergoing coronary computed tomography angiography - Al'Aref, Subhi J.; Su, Amanda; Gransar, Heidi; van Rosendael, Alexander R.; Rizvi, Asim; Berman, Daniel S.; Callister, Tracy Q.; DeLago, Augustin; Hadamitzky, Martin; Hausleiter, Joerg; Al-Mallah, Mouaz H.; Budoff, Matthew J.; et al. (Journal of Cardiovascular Computed Tomography, 2019)
Introduction: Non-statin therapy (NST) is used as second-line treatment when statin monotherapy is inadequate or poorly tolerated. Objective: To determine the association of NST with plaque composition, alone or in combination with statins, in patients undergoing coronary computed tomography angiography (coronary CTA). Methods: From the multicenter CONFIRM registry, we analyzed individuals who underwent coronary CTA with known lipid-lowering therapy status and without prior coronary artery disease at baseline. We created a propensity score for being on NST, followed by stepwise multivariate linear regression, adjusting for the propensity score as well as risk factors, to determine the association between NST and the number of coronary artery segments with each plaque type (non-calcified (NCP), partially calcified (PCP) or calcified (CP)) and segment stenosis score (SSS). Results: Of the 27,125 subjects in CONFIRM, 4,945 met the inclusion criteria; 371 (7.5%) took NST. At baseline, patients on NST had more prevalent risk factors and were more likely to be on concomitant cardiac medications. After multivariate and propensity score adjustment, NST was not associated with plaque composition: NCP (0.07 increase, 95% CI: −0.05, 0.20; p = 0.26), PCP (0.10 increase, 95% CI: −0.10, 0.31; p = 0.33), CP (0.18 increase, 95% CI: −0.10, 0.46; p = 0.21) or SSS (0.45 increase, 95% CI: −0.02,0.93; p = 0.06). The absence of an effect of NST on plaque type was not modified by statin use (p for interaction > 0.05 for all). Conclusion: In this cross-sectional study, non-statin therapy was not associated with differences in plaque composition as assessed by coronary CTA.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Coronary computed tomography angiography; Coronary plaque composition; Ezetimibe; Fibrate; Niacin; Non-statin therapy